Conditions for cross-border policy transfer and cooperation: Analysing differences between higher education and vocational training. (December 2021) - Graf, Lukas; Lohse, Anna P.
Against the backdrop of an increasingly interconnected world as well as the growing role of inter- and supranational organizations, policy transfer has become a widespread phenomenon, not least in the realm of education. While policy transfer research has focused predominantly on isolated education sectors, less is known about the overall institutional conditions that favour or inhibit policy movement in different education sectors. We argue that the conditions for cross-border policy synthesis, as a central form of policy transfer, differ systematically between the two main education sectors preparing for labour market entry, namely higher education (HE) and vocational education and training (VET). Taking the case of the cross-border region of France, Germany and Switzerland as an example, the institutional analysis shows that demand-side, programmatic, contextual and application conditions are more favourable towards cross-border policy synthesis in HE than VET.